Schooling, Political Participation, and the Economy - Campante, Filipe R.; Chor, Davin (The Review of Economics and Statistics, 2012)
We investigate how the link between individual schooling and political participation is affected by country characteristics. Using individual survey data, we find that political participation is more responsive to schooling in land-abundant countries and less responsive in human capital–abundant countries, even while controlling for country political institutions and cultural attitudes. We find related evidence that political participation is less responsive to schooling in countries with a higher skill premium, as well as within countries for individuals in skilled occupations. The evidence motivates a theoretical explanation in which patterns of political participation are influenced by the opportunity cost of engaging in political rather than production activities.